The tomaj mutant alleles of (alpha)Tubulin67C reveal a requirement for the encoded maternal specific tubulin isoform in the sperm aster, the cleavage spindle apparatus and neurogenesis during embryonic development in Drosophila. - Mathe, E.; Boros, I.; Josvay, K.; Li, K.; Puro, J.; Kaufman, T.C.; Szabad, J. (Journal of Cell Science, 1998)
The three dominant TomajD and their eleven revertant (TomajR) alleles have been localized to the alpha Tubulin67C gene of Drosophila melanogaster. Although the meiotic divisions are normally completed in eggs laid by TomajD/+, TomajD/-, TomajR/- females, embryogenesis arrests prior to the gonomeric division. The arrest is caused by: (1) the failure of prominent sperm aster formation; and (2) a consequent lack of female pronuclear migration towards the male pronucleus. Concomitant with the sperm aster defect, the four female meiotic products fuse (tetra-fusion), similar to what is seen in eggs of wild-type virgin females. In eggs of females heterozygous for weaker TomajR alleles, embryogenesis comes to a cessation before or shortly after cortical migration of cleavage nuclei. The apparent source of embryonic defect is the cleavage spindle apparatus. One of the three TomajD alleles is cold-sensitive and its cold-sensitive period coincides with the completion of female meiosis and pronuclear migration. Disorganized central and peripheral nervous systems are also characteristic of embryos derived from the temperature-sensitive TomajD/+ females. The Tomaj mutant phenotypes indicate an involvement of the normal alpha Tubulin67C gene product in: (1) the formation of the sperm aster; (2) cleavage spindle apparatus formation/function; and (3) the differentiation of the embryonic nervous system. The TomajD alleles encode a normal-sized alpha Tubulin67C isotype. Sequence analyses of the TomajD alleles revealed the replacement in different positions of a single negatively charged or neutral amino acid with a positively charged one. These residues presumably identify important functional sites.